Brevi considerazioni in materia di governance delle pratiche di culto tra istanze egualitarie, soluzioni compiacenti e protocolli (quasi) “fotocopia” (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. I pezzi si muovono sulla scacchiera - 3. Azioni e reazioni (cenni) - 4. La libertà religiosa non è a rischio: il problema sta altrove - 5. “Predicare bene e razzolare male” - 6. Un protocollo ti salva la vita - 7. Un passo avanti … e due indietro - Appendice.Short remarks on the governance of religious practices between egalitarian requests and complaisant solutionsABSTRACT: In Italy, in the context of the Covid-19 emergency, issues concerning the governance of religious practices have emerged and have been faced by different religious groups. In this contribution political and legal distortions are analyzed in the context of the non-coherent (according to the author) reading of the constitutional framework by the Italian government.